Search for a supersymmetric partner to the top quark in final states with jets and missing transverse momentum at sqrt[s] = 7 TeV with the ATLAS detector. - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; Abouzeid, O; Abramowicz, H; et al. (2012)
A search for direct pair production of supersymmetric top squarks (t(1)) is presented, assuming the t(1) decays into a top quark and the lightest supersymmetric particle, χ(1)(0), and that both top quarks decay to purely hadronic final states. A total of 16 (4) events are observed compared to a predicted standard model background of 13.5(-3.6)(+3.7)(4.4(-1.3)(+1.7)) events in two signal regions based on ∫Ldt = 4.7 fb(-1) of pp collision data taken at sqrt[s] = 7 TeV with the ATLAS detector at the LHC. An exclusion region in the t(1) versus χ(1)(0) mass plane is evaluated: 370